Adherence to outpatient cardiac rehabilitation and related factors in STEMI after PCI in China: a sequential explanatory mixed method study protocol - Wenjie Zhang; Hongjin Wang; Peiru Li; Beibei Wu; Xiaodong Wang (Frontiers in Cardiovascular Medicine)
BackgroundAcute myocardial infarction remains a major contributor to global morbidity and mortality. Cardiac rehabilitation is widely recognized as an essential component of the comprehensive medical management for patients with ST-elevation myocardial infarction, especially among those who have undergone percutaneous coronary intervention. Adherence to cardiac rehabilitation encompasses patient collaboration with a healthcare provider, active involvement in the treatment regimen, and persistence in practice, characterized by self-efficacy and relapse prevention. Outpatient cardiac rehabilitation constitutes the second phase of the continuum of care, bridging the inpatient and long-term maintenance stages. However, adherence to outpatient cardiac rehabilitation programs in China remains suboptimal. The factors influencing outpatient cardiac rehabilitation in patients with ST-elevation myocardial infarction after percutaneous coronary intervention have not yet been fully elucidated.AimsTo investigate the status and influencing factors of adherence to outpatient cardiac rehabilitation in patients with ST-elevation myocardial infarction after percutaneous coronary intervention one month after discharge in China and gain a deeper understanding of this phenomenon of interest.MethodsAn explanatory sequential mixed-methods design will be employed to conduct this study with three phases. The first phase is a quantitative study with a cross-sectional design to assess the level of adherence to outpatient cardiac rehabilitation and related influences based on the Health Belief Model among 198 patients with ST-elevation myocardial infarction after percutaneous coronary intervention in two tertiary hospitals in Zhenjiang, Jiangsu Province, China. The second phase is followed by a qualitative study to explore the patients’ perceived facilitators and barriers to adherence to outpatient cardiac rehabilitation. Purposive sampling, semi-structured interviews, and conventional content analysis approaches will be used to collect and analyze the data. The final phase links to integrating the data and developing a targeted strategy to improve adherence to outpatient cardiac rehabilitation among patients with ST-elevation myocardial infarction after percutaneous coronary intervention. The nominal group technique and "weaving techniques" will be implemented in accordance with the results of the preceding two phases.DiscussionA targeted strategy to improve outpatient cardiac rehabilitation adherence would be designed considering the factors affecting adherence to outpatient cardiac rehabilitation in patients with ST-elevation myocardial infarction after percutaneous coronary intervention. Clinical Trial RegistrationThis study has been registered in the Chinese Clinical Trial Registry: ChiCTR2400080035.